Highly Qualified Personnel as A Factor in Increasing Economic Growth in Uzbekistan - OCHILOV, AKRAM; RUZIYEV, ZAFAR; BABAYEVA, LOLA; GANIYEVA, SHARIFA (International Journal of Psychosocial Rehabilitation, 2020)
This article describes how accumulated knowledge is becoming as a driving force of economic growth and social development in Uzbekistan. In the article the achievements and challenges of education and innovation systems and their role in fostering of economic growth of Uzbekistan investigated. Education is admitted to be one of the driving forces of the knowledge based economy. In particular, along with the capital and human resources the quantity and quality of education in general, higher education particularly, may have significant effect on economic growth. The research attempted to determine the existence of correlation between quantity/quality of higher education and the economic growth in Uzbekistan. Regression estimation with GDP growth as dependent variable and number and quality of graduates, per graduator costs as well as accumulated average year of schooling as independent variables revealed strong relationship between higher education and economic growth in Uzbekistan.